The impact of the integration associations on the development of the export potential of Ukraine - DESYATNYUK, Oksana; VOITSESHYN, Vasyl (Scientific journal «World of Finance», 2019)
Introduction. The development of the economy of Ukraine is directly determined by the value of the export of products, in particular, in the long-term perspective, that is, in the future, which is expressed in the export potential, which allows us to assess the level of the economic power of the state and the ability to furtherits development. The deepening of the economic integration of Ukraine, expressed in its participation in the integration associations, when Ukraine has recently become a full member of the European Union (EU) , actualizes the issue ofthe development ofits exportpotential, afterall, the Ukraine’s membership in the EU obliges it to implement its norms into the national economy, including the trade (as certifies by the participation of Ukraine in the World Trade Organization (WTO), which directly affects on its export. Purpose. This research sets up an assessment ofthe impact ofthe membership of Ukraine in the WTO and the EU, in part ofits contractual commitments on its exportpotential. Methods. In this research we used a cross-correlation and a correlation-regression analysis. Results. In the course of this research we found that the effect ofthe membership of Ukraine in the WTO and the EU on the export potential is controversial, because with the expansion of the partnership and the sales markets ofthe products and the strengthening ofits competitiveness, a crisis has emerged in the Ukrainian economy generated by a regional integration, which has had a negative impact on the export potential of Ukraine. Conclusion. This research proposes following conclusions and recommendations for improving the impact ofintegration associations on the development of the export potential of Ukraine: • the search forsolutions to the military-political crisis in Ukraine; • trade liberalization in the context ofthe gradual abolition of export duties on goods with the addition ofa new schedule ofremovating ofthe export duties.